DARI OTOKRASI KE DEMOKRASI: MENYIBAK SEJARAH DAN SURVIVALITAS “DEMOKRASI ALA DAERAH ISTIMEWA YOGYAKARTA” - Emilianus Yakob Sese Tolo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
Nowadays, western-styled democracy is regarded as the best system of governance. Therefore, there is a global tendency to make western-styled democracy to be implemented across the globe. In Yogyakarta Special Region (DIY), the introduction of western-styled democracy was wellaccepted. The values of western democracy was merged with the Javanese political culture to form a “demokrasi ala DIY”. This article aims to analyze the positive relation between western-styled democracy and political culture in DIY, by using qualitative description methodology. The article concludes that Javanese political culture does support the process of democratization. The two dynasties of Hamengkubuwono and Pakualaman do contribute for the change from autocracy to democracy and the establishment of “demokrasi ala DIY”.